Autosomal Recessive Congenital Ichthyosis in American Bulldogs Is Associated With NIPAL4 (ICHTHYIN) Deficiency. (July 2015) - Mauldin, E. A.; Wang, P.; Evans, E.; Cantner, C. A.; Ferracone, J. D.; Credille, K. M.; Casal, M. L.
A minority of patients with nonsyndromic autosomal recessive congenital ichthyosis (ARCI) display mutations in NIPAL4 ( ICHTHYIN ). This protein plays a role in epidermal lipid metabolism, although the mechanism is unknown. The study describes a moderate form of ARCI in an extended pedigree of American Bulldogs that is linked to the gene encoding ichthyin. The gross phenotype was manifest as a disheveled pelage shortly after birth, generalized scaling, and adherent brown scale with erythema of the abdominal skin. Pedigree analysis indicated an autosomal recessive mode of inheritance. Ultrastructurally, the epidermis showed discontinuous lipid bilayers, unprocessed lipid within corneocytes, and abnormal lamellar bodies. Linkage analysis, performed by choosing simple sequence repeat markers and single-nucleotide polymorphisms near genes known to cause ACRI, revealed an association with NIPAL4. NIPAL4 was identified and sequenced using standard methods. No mutation was identified within the gene, but affected dogs had a SINE element 5′ upstream of exon 1 in a highly conserved region. Of 545 DNA samples from American Bulldogs, 32 dogs (17 females, 15 males) were homozygous for the polymerase chain reaction fragment. All affected dogs were homozygous, with parents heterozygous for the insertion. Immunolabeling revealed an absence of ichthyin in the epidermis. This is the first description of ARCI associated with decreased expression of NIPAL4 in nonhuman species.